Nutrient requirements of growing Angora rabbits - SINGH, GEETANJALI; SHARMA, K S; KUMARI, MEENA; KATOCH, B S (The Indian Journal of Animal Sciences, 2013)
Angora rabbit kits (25), 40-day-old were equally distributed on almost equal average body weight basis into 5 groups and allotted to 5 test diet treatments with 5 kits in each treatment and fed up to 140 days of age. Out of 5 test diets fed for 100 days, 02 test diet CP- 17.25%, lysine (0.69%, threonine-0.63%, methionine + cystine-0.69% and DE-2875 Kcals/kg)showed the best growth performance by showing significantly highest (P